Relationship between psychoeducation and treatment adherence in adults with depression at the National Institute of Mental Health Honorio Delgado-Hideyo Noguchi, 2018-2023 - Carazas-Vera, María Soledad (2024)
Depression is a public health problem that leads to disability and a decreased quality of life. Multiple studies point out the effectiveness of psychoeducation as part of its treatment. Objective: To determine the relationship between structured psychoeducation and adherence to treatment in adults patients with depression treated at the National Institute of Mental Health “Honorio Delgado-Hideyo Noguchi” (INSM HD-HN). Methodology: Observational, analytical, retrospective and transversal study, in which the clinical records of 536 adult patients with a diagnosis of a depressive disorder (DD) were reviewed, 268 of them exposed to psychoeducation and 268 not exposed, were included. Results: A significant association between structured psychoeducation and adherence to treatment (x2=125.26; p=0.000) was evident. Similarly, an association was found between dropping out of treatment and not having received structured psychoeducation (x2=10.12; p=0.001). A 40.1% of people with DD adhered to the treatment, 57.6% attended regularly their medical appointments, 72% dropped out during the follow-up period, and 40.3% adhered to psychoeducation. Age, (x2=22.59; p=0.000), marital status (x2=15.45; p=0.009), occupation (x2=15.29; p=0.000) and comorbidity (x2=12.406; p=0.006) were also associated with adherence to treatment. Conclusions: Adherence to treatment is low in the studied sample while the dropout level during the follow-up period is high. A well structured psychoeducation, predominantly of an individual nature is an important factor to achieve greater adherence and less desertions of treatment among depressed patients. Variables related to greater adherence to treatment were age over 60 years, married marital status, home working, and having a concurrent physical comorbidity.